1996
DOI: 10.1111/j.1476-5381.1996.tb15696.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclic GMP elevation on isoprenaline‐induced increase in cyclic AMP and relaxation in rat aortic smooth muscle: role of phosphodiesterase 3

Abstract: 1In rat aortic rings precontracted with phenylephrine, the P-adrenoceptor agonist isoprenaline (10 nM to 30 gM) produces greater relaxant effects in preparations with endothelium than in endotheliumdenuded preparations. The aim of this study was to determine the mechanisms involved in this effect and in particular investigate the possibility of a synergistic action between adenosine 3': 5'-cyclic monophosphate (cyclic AMP) and guanosine 3': 5'-cyclic monophosphate (cyclic GMP). 2 Isoprenaline-induced relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 30 publications
4
57
1
1
Order By: Relevance
“…The proportion of NO-independent relaxation induced by isoprenaline in small pulmonary arteries was similar to that previously described in rat small mesenteric arteries (Graves & Poston, 1993). Our results are in clear agreement with previous studies on systemic arteries, that have suggested that isoprenaline-induced relaxation is at least partly dependent on NO and the endothelium (Gray & Marshall, 1992;Blankesteijn & Thien, 1993;Graves & Poston, 1993;Delpy et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The proportion of NO-independent relaxation induced by isoprenaline in small pulmonary arteries was similar to that previously described in rat small mesenteric arteries (Graves & Poston, 1993). Our results are in clear agreement with previous studies on systemic arteries, that have suggested that isoprenaline-induced relaxation is at least partly dependent on NO and the endothelium (Gray & Marshall, 1992;Blankesteijn & Thien, 1993;Graves & Poston, 1993;Delpy et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…However Graves & Poston (1993) showed a slight enhancement of forskolininduced relaxation in the presence of L-NAME in rat mesenteric arteries, and Kuhn et al (1991) were unable to demonstrate any increase in NO release from bovine cultured endothelial cells following experimental increases in cyclic AMP. Our results in pulmonary arteries are more similar to those of Delpy et al (1996) than Gray & Marshall (1992), in that the forskolin concentration-response curve was shifted to the right by L-NMMA, with no change in maximum relaxation. In direct contrast to the b-agonists examined in our preparation, forskolin was a more e ective vasodilator in large as opposed to small pulmonary arteries.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…There is known to be signi®cant cross-talk between cyclic AMP and cyclic GMP pathways (Lincoln & Cornwell, 1993;Vigne et al, 1994), and activators of guanylate cyclase have been shown to potentiate isoprenaline stimulated cyclic AMP accumulation and relaxation in vascular smooth muscle (Maurice & Haslam, 1990;Delpy et al, 1996). However PE has also been shown to stimulate or potentiate accumulation of cyclic AMP directly in a variety of other cell types (Pedarzani & Storm, 1996;Traish et al, 1997;Ruan et al, 1998), although there are few reports on vascular smooth muscle (Izumi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%